1985
DOI: 10.1111/j.2044-8317.1985.tb00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness measurement with polychotomous item response models and standardized indices

Abstract: The test scores of some examinees on a multiple choice test may not provide satisfactory measures of their abilities. The goal of appropriateness measurement is to identify such individuals. Earlier theoretical and expcrimcntal work considered examinees answering all, or almost all, test items. This article reports research that extends appropriateness measurement methods to examinees with moderately high non-response ratcs. These methods treat non-response as if it were a deliberate option choice and then att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
428
1
10

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(442 citation statements)
references
References 10 publications
3
428
1
10
Order By: Relevance
“…Baumert et demmrich (2001) définissent la motivation à passer une épreuve comme étant « la volonté de s'impliquer à répondre aux items de l'épreuve et d'investir effort et persistance à l'activité entreprise » (traduction libre, p. 441). la revue de la littérature révèle que l'approche de l'élève vis-à-vis des enquêtes à grande échelle influence significativement ses résultats (drasgow, levine, & williams, 1985 ;Glas & Falcón, 2003 ;Glas & Meijer, 2003 ;levine & rubin, 1979 ;nering, 1997 ;van Krimpen-stoop & Meijer, 1999). un corpus grandissant de recherches décrit le phénomène à travers lequel l'élève ne mobilise pas toutes ses ressources et ne fournit pas nécessairement l'effort attendu pour remplir le test lorsque ce dernier n'a pas ou peu de conséquence personnelle (Baumer & demmrich, 2001 ;Blau, Moller, & Jones, 2004 ;deMars, 2000 ;eklöf, 2010 ;Ferrer-caja & weiss, 2002 ;hoyt, 2001 ;olaru, Karageorghis, & chatzisarantis, 2003 ;sloane & Kelly, 2003 ;van Barneveld et al, 2012 ;wise, 1996a, 1996bwise & demars, 2005 ;wolf & smith, 1995 ;wolf, smith, & Birnbaum, 1995).…”
Section: Contexteunclassified
“…Baumert et demmrich (2001) définissent la motivation à passer une épreuve comme étant « la volonté de s'impliquer à répondre aux items de l'épreuve et d'investir effort et persistance à l'activité entreprise » (traduction libre, p. 441). la revue de la littérature révèle que l'approche de l'élève vis-à-vis des enquêtes à grande échelle influence significativement ses résultats (drasgow, levine, & williams, 1985 ;Glas & Falcón, 2003 ;Glas & Meijer, 2003 ;levine & rubin, 1979 ;nering, 1997 ;van Krimpen-stoop & Meijer, 1999). un corpus grandissant de recherches décrit le phénomène à travers lequel l'élève ne mobilise pas toutes ses ressources et ne fournit pas nécessairement l'effort attendu pour remplir le test lorsque ce dernier n'a pas ou peu de conséquence personnelle (Baumer & demmrich, 2001 ;Blau, Moller, & Jones, 2004 ;deMars, 2000 ;eklöf, 2010 ;Ferrer-caja & weiss, 2002 ;hoyt, 2001 ;olaru, Karageorghis, & chatzisarantis, 2003 ;sloane & Kelly, 2003 ;van Barneveld et al, 2012 ;wise, 1996a, 1996bwise & demars, 2005 ;wolf & smith, 1995 ;wolf, smith, & Birnbaum, 1995).…”
Section: Contexteunclassified
“…In this section, we will briefly explain the popular residual fit statistics (Wright & Masters, 1982) of the Rasch model, implemented in the software WINSTEPS (Linacre & Wright, 1999). Discussions of other diagnostic indices can be found in Drasgow, Levine, and Williams (1985). The starter data example is used to illustrate the computations of these fit statistics as implemented by PROC IML (Interactive Matrix Language) using output from PROC NLMIXED.…”
Section: Goodness Of Fitmentioning
confidence: 99%
“…In person-fit area, Wollack (1997), Drasgow, Levine, and Williams (1985) were used distractor information to detect aberrant response behaviors. Kim (2006) found that linking procedure was improved when distractor information was added in.…”
Section: Introductionmentioning
confidence: 99%